Infections of the genital tract in women with verified laparoscopy of the pathology of the fallopian tubes and normal laparoscopic results - S.O.Dubrovina; O.A.Ardintseva (IP Berlin A.V., 2018)
Introduction. Pipe and peritoneal factors are important causes of infertility and inflammatory diseases of the pelvic organs (PID). It is well known that Neisseria gonorrhoeae and Chlamydia trachomatis are etiologic agents of pelvic inflammation leading to infertility. There is a very limited number of publications about which representatives of sexually transmitted infections (STIs) or other microorganisms can be found in the fallopian tubes during reconstructive plastic surgery. Knowledge in this area is necessary for the proper selection of antibiotic therapy during and after operations. The purpose of our study is to determine the microbial landscape of the contents of the fallopian tubes in infertile patients with a tubal peritoneal infertility factor diagnosed during laparoscopy and normal uterine tubes. Materials and methods. 22 women with infertility were included in the study. 12 of them (the main group) had tubal peritoneal pathology, 10 women had no pathology of the fallopian tubes (control group). The average age of patients in the first group was 25 years (20-29), in the control group - 31 years (20-36). For all women, laparoscopy was part of the infertility survey. In the 1 st group, the changes in the fallopian tubes according to the type of fibrosis, hydrosalpinx or adhesions in the region of the periampulal or fimbrial part were identified. During laparoscopy, the fallopian tubes were washed with 2-4 ml of saline immediately after laparoscopic and laparoscopic instruments. Through the lateral trocar, the material was taken from the fallopian tubes using a bacteriological loop to perform bacteriological inoculation. Identification of the DNA of the pathogens was carried out by the polymerase chain reaction method according to the instructions. Identification and sensitivity determination of the isolated cultures was performed using an automatic bacteriological analyzer Vitek 2 Compact 30. Results. In all women without an identification of STIs and PID in the history and absence of abnormalities of the fallopian tubes in laparoscopy (control group), we did not find any microorganisms in the fallopian tubes. We did not detect C. trachomatis, N. gonorrhoeae or Trichomonas vaginalis in the fallopian tubes. However, we found twice Ureaplasma urealyticum in the fallopian tubes (16.7%), while in the control group this microorganism was also detected once. An important feature of salpingitis is extensive tissue remodeling, leading to chronic effects, such as scarring and obstruction, during which STIs and other microorganisms are eliminated by the immune system. In this study, we identified twice in the fallopian tubes of U. urealyticum. Perhaps U. urealyticum persists after antibiotic therapy and selective elimination of the main pathogens, since certain antibiotics affect the cell wall that is absent in this microorganism.